2016
DOI: 10.5492/wjccm.v5.i1.96
|View full text |Cite
|
Sign up to set email alerts
|

Mild to moderate intra-abdominal hypertension: Does it matter?

Abstract: This review summarizes the epidemiology, pathophysiological consequences and impact on outcome of mild to moderate (Grade I to II) intra-abdominal hypertension (IAH), points out possible pitfalls in available treatment recommendations and focuses on tasks for future research in the field. IAH occurs in about 40% of ICU patients. Whereas the prevalence of abdominal compartment syndrome seems to be decreasing, the prevalence of IAH does not. More than half of IAH patients present with IAH grade I and approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
14
0
5
Order By: Relevance
“…9 Our findings have been supported by the work of Maddison et al . 24 We found that as the IAP increases to 20 mm Hg for 90 min, intestinal barriers become seriously disrupted and dysbiosis occurs. 25 However, in the present study, at the same level of IAH, MICU1 exhibited a compensatory response towards the increased intestinal permeability, indicating that under IAH, the gut promotes a self-protective mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…9 Our findings have been supported by the work of Maddison et al . 24 We found that as the IAP increases to 20 mm Hg for 90 min, intestinal barriers become seriously disrupted and dysbiosis occurs. 25 However, in the present study, at the same level of IAH, MICU1 exhibited a compensatory response towards the increased intestinal permeability, indicating that under IAH, the gut promotes a self-protective mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…3 IAH frequently appears in patients who develop an inflammatory process inside the abdominal cavity and can be further exacerbated by the excessive fluid therapy in these cases. 6 An increase of IAP has been proved to be associated with a significant reduction of the splanchnic blood flow. 16,17 Intraoperative and postoperative optimization of fluid administration has been proved to be strongly associated with a reduction in mortality in critically ill patients; however, in a study by Liu et al, static preload variables represented by central venous pressure and pulmonary capillary wedge pressure were not able to predict the cardiac response to fluid therapy in patients with IAH.…”
Section: Fluid Balance Preload and Iapmentioning
confidence: 99%
“…5 Abdominal compartment syndrome represents the final stage of a severe condition characterized by an increase in IAP to a degree that compromises the regional blood flow in vital abdominal organs. 6 Abdominal compartment syndrome is considered nowadays a life-threatening condition, being associated with significant deterioration in cardiac, renal, and respiratory function. 4 Therefore, in mechanically ventilated patients, all the necessary therapeutic measures should be undertaken in order to prevent the progression of IAH to more severe stages and abdominal compartment syndrome.…”
mentioning
confidence: 99%
“…Patients at risk of developing IAH/ACS can be divided into two categories: patients who suffer an increase of the intraabdominal content volume and patients with decreased abdominal volume (management of abdominal wall defects). Both groups can be characterized by an increase of the IAP values, but patients in the first category are prone to further decompensation subsequently to ischemia-reperfusion injuries in the mesenteric area accompanied by the need for hydric resuscitation [IAH occurs in about 40% of the intensive care unit patients (3)]. This type of evolution can only further increase the degree of edema and consequently leads to the intolerance of IAP rise.…”
Section: Introductionmentioning
confidence: 99%